2013
DOI: 10.1128/ec.00359-12
|View full text |Cite
|
Sign up to set email alerts
|

Three Prevacuolar Compartment Rab GTPases Impact Candida albicans Hyphal Growth

Abstract: Disruption of vacuolar biogenesis in the pathogenic yeast Candida albicans causes profound defects in polarized hyphal growth. However, the precise vacuolar pathways involved in yeast-hypha differentiation have not been determined. Previously we focused on Vps21p, a Rab GTPase involved in directing vacuolar trafficking through the late endosomal prevacuolar compartment (PVC). Herein, we identify two additional Vps21p-related GTPases, Ypt52p and Ypt53p, that colocalize with Vps21p and can suppress the hyphal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 54 publications
(70 reference statements)
2
36
0
Order By: Relevance
“…Strain THE1 was kindly provided by H. Nakayama and M. Arisawa (Nippon Roche) (19). pKEtetO4 was previously described and is based on plasmid pLUX (20). pKEtetO4 harbors the tetO promoter and the 3= untranslated region (UTR) of the C. albicans ADH1 gene, separated by a multiple-cloning site (MCS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain THE1 was kindly provided by H. Nakayama and M. Arisawa (Nippon Roche) (19). pKEtetO4 was previously described and is based on plasmid pLUX (20). pKEtetO4 harbors the tetO promoter and the 3= untranslated region (UTR) of the C. albicans ADH1 gene, separated by a multiple-cloning site (MCS).…”
Section: Methodsmentioning
confidence: 99%
“…This was confirmed by PCR using primers LUXINTF (5=-CTGACCTTTAGTCTTTCCTG C-3=) and LUXINTR (5=-CAGTAGTACTTGTTGTTGTATCG-3=). An isogenic control strain (TT21), made by transforming the pKEtetO4 vector alone into THE1, was previously described, as was the isogenic TUME6 strain (20).…”
Section: Methodsmentioning
confidence: 99%
“…All strains used in this study are listed in Table S2 in the supplemental material. The vps21⌬/⌬, aps3⌬/⌬, and vps21⌬/⌬ aps3⌬/⌬ mutants were constructed in previous studies (13,14,16,17). Control strain YJB6284 (18) was kindly provided by Judith Berman (Tel Aviv University).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pLUX (12) was kindly provided by William Fonzi (Georgetown University). Plasmids pLUXVPS21 (13), pKE1 (14), and pKE1-NLUC (15) were described previously. All oligonucleotides used in this study are listed in Table S1 in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
“…Hyphal tip growth requires intracellular compartments, vesicles, and trafficking. For example, it has been shown that prevacuolar compartment RabGTPases impact hyphal growth [49]; that the protein Sec2p is physically associated with SEC2 mRNA on secretory vesicles [45]; and that vacuolar acidification is essential for morphology and virulence [50]. One new, but related, aspect of hyphal growth and pathogenicity is hyphal branching, which precise role still remains to be elucidated [51,52].…”
mentioning
confidence: 99%